2008
DOI: 10.1136/emj.2007.053090
|View full text |Cite
|
Sign up to set email alerts
|

Can a change in policy reduce emergency hospital admissions? Effect of admission avoidance team, guideline implementation and maximising the observation unit

Abstract: A multidisciplinary emergency department policy, using as much available evidence as possible, was successful in significantly reducing medical hospital admissions in spite of the rising numbers of patients visiting the emergency department and observation unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…The hospital admission rate in our cohort (4.1%), in keeping with recent U.S. data, represents a reduction from previous (8.2%) identified employing the same data set 5 years earlier . This may represent improvements in management, including the use of novel therapeutics or implementation of policies designed to reduce admissions to overcome inpatient bed shortages . Our study, which was designed to evaluate whether the implementation of embedded, evidence‐based care strategies was associated with the aforementioned improvements, found that the existence of order sets, pathways, and medical directives was not associated with reductions in admissions.…”
Section: Discussionsupporting
confidence: 78%
“…The hospital admission rate in our cohort (4.1%), in keeping with recent U.S. data, represents a reduction from previous (8.2%) identified employing the same data set 5 years earlier . This may represent improvements in management, including the use of novel therapeutics or implementation of policies designed to reduce admissions to overcome inpatient bed shortages . Our study, which was designed to evaluate whether the implementation of embedded, evidence‐based care strategies was associated with the aforementioned improvements, found that the existence of order sets, pathways, and medical directives was not associated with reductions in admissions.…”
Section: Discussionsupporting
confidence: 78%
“…In addition, we found that correlates of ED use were heterogeneous based on location in an urban versus suburban or rural region. Thus, public health policy solutions for improving the delivery of acute care must consider that the effect of interventions will depend on the population in question, and that there appears to be interactive effects of geography and population characteristics [3,47]. We believe our methods allow for a nuanced understanding of community health and the drivers of ED utilization that will inform the development of targeted interventions for geographic areas and local populations with high ED use.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that early assessment by experienced doctors and nurses in an emergency department reduces emergency admissions. 16–18 There is a large literature that examines how to improve processes within an emergency department, but little of this measures patient-orientated outcomes. 19–24 Future work should attempt to validate these findings across different hospitals.…”
Section: Discussionmentioning
confidence: 99%